Geometrical Axon Guidance with PDMS Microstructures - Speicher, Sandra Ines (My University, 2016)
Having circuits made of single neurons would bring us a big step closer to a full understanding of the neuronal system. To build these networks and more, we need to find a way to guide axons in specific directions. Learning about their turning behavior in predefined geometric environments was the scope of this project. In order to enable a statistical analysis of the axons’ behaviors in geometrically defined environments, microstructures with repetitive patterns of T-junction channels were designed in AutoCAD and fabricated in polydimethylsiloxane (PDMS) from SU8 molds that had been made using photolithography. The design of the T-junctions was varied in different parameters such as the angle of incident of the upstroke of the ’T’ against the horizontal stroke or the relocation of the upstroke closer towards one side of the horizontal stroke. These structures were stuck onto laminin or poly-D-lysine (PDL) coatedWillCo dishes and seeded with primary cortical rat neurons. The neurons were transfected with a viral vector to enable fluorescence imaging with a confocal laser scanning microscope (CLSM).The time frame of the project did not allow for the performance of a statistical analysis, but important milestones were set for the preparation thereof. Structure designs that aid an automatized imaging process were found, the fragile culturing conditions primary neurons need to stay alive and grow axons were met and the automatization of the imaging itself was successfully implemented. A trend in the axon bending behavior was recognized.
Keywords: Informations- och kommunikationsteknik; Materialvetenskap; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Fysik; Information & Communication Technology; Materials Science; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Physical Sciences